Orchestration of Immunological Synapse Assembly by Vesicular Trafficking - Onnis, Anna; Baldari, Cosima T. (Frontiers in Cell and Developmental Biology, 2019)
Ligation of the T-cell antigen receptor (TCR) by cognate peptide bound to the Major Histocompatibility Complex on the surface of an antigen-presenting cell (APC) leads to the spatial reorganization of the TCR and accessory receptors to form a specialized area of intimate contact between T cell and APC, known as the immunological synapse (IS), where signals are deciphered, coordinated and integrated to promote T cell activation. With the discovery that an endosomal TCR pool contributes to IS assembly and function by undergoing polarized recycling to the IS, recent years have witnessed a shift from a plasma membrane-centric view of the IS to the vesicular trafficking events that occur at this location following the TCR-dependent translocation of the centrosome towards the synaptic membrane. Here we will summarize our current understanding of the trafficking pathways that are responsible for the steady delivery of endosomal TCRs, kinases and adapters to the IS to sustain signaling, as well as of the endocytic pathways responsible for signal termination. We will also discuss recent evidence highlighting a role for endosomes in sustaining TCR signaling after its internalization at the IS and identifying the IS as a site of formation and release of extracellular vesicles that allow for transcellular communicaiton with the APC.